Determination of Stability Constants of Thallium(I) Complexes with Diglycolic Acid - Meena, Suman; Sharma, Jitender; Gupta, O.D. (Asian Journal of Chemistry, 2010)
The reduction of Tl(I) with diglycolic acid has been investigated electrochemically in aqueous medium and the stability constants of complexes formed by Tl(I) with diglycolic acid have been evaluated. The values of stability constants of complexes of Tl(I) with diglycolic acid are log b1 = 3.477, log b2 = 6.5051 at temperature 308 K and log b1 = 3.0791, log b2 = 5.8976 at temperature 313 K which have been calculated by DeFord and Hume's method. The mathematical Mihailov's method was also used.